Effect of basic fibroblast growth factor on expression of protein and mRNA of bone morphogenetic protein 4 in hypoxic-ischemic brain damage in newborn rats - Yin, Xiao-juan (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2009)
OBJECTIVE: To investigate the effect of basic fibroblast growth factor(bFGF) on expression of protein and mRNA of bone morphogenetic protein 4 in hypoxic-ischemic brain damage (HIBD) in newborn rats